Oral health of children with type 1 diabetes mellitus: a systematic review - Ismail, Ahmad Faisal; McGrath, Colman Patrick; Yiu, Cynthia (Elsevier, 2015)
Aim: This systematic review investigated the oral health status of children with type 1 diabetes. Methods: A systematic search was conducted using PubMed/Medline, Web of Knowledge, SCOPUS and EMBASE. The search included all studies published from inception of database to January 2014. A total of 1179 abstracts were analyzed for selection in 2 phases. The first phase selection was based on the title and abstracts alone. The selected abstracts were then included for second phase, where full articles were obtained. The selection was carried out by 2 independent reviewers (Kappa value = 0.809). Only 37 articles were included for final analysis in this review. Results: There is conflicting evidence in the caries experience between children with type 1 diabetes and healthy children. For periodontal health, most studies reported significantly greater plaque accumulation and higher gingival index in children with type 1 diabetes. Cohort studies reported no significant differences in perioodontal parameters over time. Conclusions: There is conflicting evidence regarding the caries experience of children with type 1 diabetes, but they exhibit poorer periodontal health status with greater plaque accumulation compared to healthy children. Further studies are warranted to assess the oral health status of children with type 1 diabetes.